Listening to Bedouin fathers of children with autism spectrum disorder. (April 2019) - Manor-Binyamini, Iris
Although children across the world experience autism spectrum disorder (ASD), most research on ASD has been conducted using Western cultural perspectives and has focused primarily on mothers, leaving significant gaps in the literature. This study aimed to address these gaps by exploring the experiences of fathers raising children with ASD in a Bedouin community. To this end, a sample of 19 fathers of children (aged 6–15 years) with ASD living in recognized and unrecognized Bedouin settlements in the Negev participated in ethnographic, semi-structured interviews designed to investigate their experiences with raising a child with ASD in their community. Two major themes emerged: the challenges that Bedouin fathers of children with ASD face, and the influence of socio-demographic and cultural characteristics on their experience. Findings reflect the complex experiences of fathers raising children with ASD in the Bedouin community, stemming from their socio-cultural context and the limited knowledge and support services that are available in the community for these children. This article concludes with recommendations on how to enhance professional sensitivity and provide more culturally tailored services for parents of children with ASD.